Addressing Major Health Disparities Related to Coronavirus for People With Behavioral Health Conditions Requires Strength‐Based Capacity Building and Intentional Community Partnership. Issue 3 (27th August 2020) - Progovac, Ana M.; Cortés, Dharma E.; Chambers, Valeria; Adams, Leslie B.; Jean‐Claude, Soso; Willison, Charley E.; Flores, Michael; Creedon, Timothy B.; Cook, Benjamin L.
Abstract : Far from being an equalizer, as some have claimed, the COVID‐19 pandemic has exposed just how vulnerable many of our social, health, and political systems are in the face of major public health shocks. Rapid responses by health systems to meet increased demand for hospital beds while continuing to provide health services, largely via a shift to telehealth services, are critical adaptations. However, these actions are not sufficient to mitigate the impact of coronavirus for people from marginalized communities, particularly those with behavioral health conditions, who are experiencing disproportional health, economic, and social impacts from the evolving pandemic. Helping these communities weather this storm requires partnering with existing community‐based organizations and local governments to rapidly and flexibly meet the needs of vulnerable populations.